Influence of cutting tool angles on the formation of built-up-edge - Hossain, Md. Bellal; Khan, Ahsan Ali; Karim, A.N. Mustafizul (2000)
This paper presents the results of investigating the effect of tool geometry on the formation of built-up-edge (BUE). Side cutting and rake angles of the cutting tool were chosen for the study. Initially the experiments were conducted by one-variable-at-a-time approach to identify the range of angles influencing BUE. Both the angles of the cutting tool were found to influence the BUE height. For a set value of the rake angle, a peak of BUE height was observed with the change of side cutting angle. An interactive effect of both the parameters of the tool geometry was observed on the formation of the BUE. An attempt was subsequently made to develop a model by adopting an approach of design of experiment. The model developed indicated that at higher range of the rake angle, the increase of side cutting angle would have very little influence on the height of BUE. But at lower rake angle (-15 to 15 deg) height of BUE was found to decrease rapidly with the increase of side cutting angle. For a set value of side cutting angle, the increase in rake angle of the tool would lead to increase in the height of BUE.